PENGARUH KECERDASAN EMOSI (EQ) DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI BELAJAR MAHASISWA AKPARNAS-UNAS JAKARTA - Tine Yuliantini (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: The research aims to analyze the influence of emotional intelligence andachievement motivation to achievement in learning ofstudents in Akparnas UnasJakarta.The Research is descriptive research with used regression analysis andcorrelation with data of questionnaire collected from the all students at Akparnas UnasJakarta.The result of research showed that Emotional intelligence and achievementmotivation have a positive and significant effect to achievement in learning. The variableachievement motivationis the most dominant variable to influence achievement inlearning with almost powerful dimension is the dimension of need of achievement.Keywords: emotional intelligence, achievement motivation dan achievement in learning